Development of Android-Based Learning Media on Smoked Fish Integrated Additive Material in Bengkulu City: Pengembangan Media Pembelajaran Berbasis Android Pada Materi Zat Aditif Terintegrasi Ikan Asap Di Kota Bengkulu - Pancarani, Dwi Ayu; Uliyandari, Mellyta; Parlindungan, Deni; Nirwana, Nirwana; Risdianto, Eko (Universitas Muhammadiyah Sidoarjo, 2024)
This research was conducted because of the difficulties experienced by students in learning, especially in the use of learning resources which still use printed books and worksheets in less interesting classroom learning. The gap that occurs between expectations and reality is that students expect learning to be more interactive, interesting and practical. This research aims to produce Android-based learning media products using integrated additives as smoked fish in the city of Bengkulu. The method applied is research and development (RND). This research uses a 4D development model (Define, Design, Development, and Disseminate). Development carried out is limited to the Development stage. The subjects of this research were 31 students in class VIII 2 of SMPN 3 Bengkulu City. Research instruments include observation, teacher interview sheets, student readability test sheets and expert validation sheets. The results of the research show that Android-based learning media on integrated smoked fish additive material is very suitable for use based on validation results from two validators, namely two material experts, two media experts, and practitioners. The learning media validation score by material experts was 88 in the